Identification of the slow reacting substances from cat paws. - Houglum, J (1980)
Perfusion of cat paws with compound 48/80 released two slow reacting substances (SRSs) which were isolated and characterized as 5-hydroxy-6-S-cysteinylglycyl-7,9,11,14-icosatetraenoic acid (SRS I) and 5-hydroxy-6-S-cysteinyl-7,9,11,14-icosatetraeonic acid (SRS II) on the basis of chemical degradations, amino acid analyses, spectroscopic and enzymic experiments, and comparison with synthetic samples. The smooth muscle-contractile activities of synthetic 5-hydroxy-6-gamma-glutamylcysteinylglycyl-7,9,11,14-icosatetraenoic acid, synthetic 5-hydroxy-6-S-cysteinyl-7,9,11,14-icosatetraenoic acid, and SRS II were not inactivated by arylsulfatase. On the other hand, the spasmogenic activities produced by synthetic 5-hydroxy-6-S-cysteinylglycyl-7,9,11,14-icosatetraenoic acid and SRS I were destroyed at the same rate by the arylsulfatase. This mode of inactivation was attributed to an aminopeptidase activity in the arylsulfatase preparation because 5-hydroxyl-6-S-cysteinyl-7,9,11,14-icosatetraenoic acid was isolated and identified as the reaction end product. Because the properties of SRS from cat paws closely resemble those of SRS generated by immunological stimulation of human tissues (SRS-A) and because all known SRS-A are inactivated by arylsulfatases, we contend that 5-hydroxy-6-S-cysteinylglycyl-7,9,11-14-icosatetraenoic acid (SRS I) corresponds to SRS-A.